Seasonal variation in soil algal community structure in different forest plantations in subtropic China - Wei, Liman; Zhao, Qiong; Chen, Xiangyu; Sun, Qingye; Zhang, Xiang; Chen, Yongjing (Frontiers in Plant Science, 2023)
Algae exert great impact on soil formation and biogeochemical cycling. However, there is no full understanding of the response of soil algal community structure to the seasonal fluctuations in temperature and moisture and changes of soil physicochemical properties across different forests.Here, based on 23S rRNA gene sequencing, we analyzed soil algal community structure in four different forest plantations in two seasons and examined soil physiochemical properties. The results showed the significantly seasonal variation in soil algal community structure, with the higher overall diversity in summer than in winter. In addition, there existed significant correlations between soil algae (species composition, relative abundance, diversity index) and physicochemical properties (pH, total phosphorus, organic matter and nitrate nitrogen), suggesting that edaphic characteristics are also largely responsible for the variation in soil algal community. Nevertheless, the seasonal variation in algal community structure was greater than the variation across different forest plantations. This suggest temperature and moisture are more important than soil physicochemical properties in determining soil algal community structure. The findings of the present study enhance our understanding of the algal communities in forest ecosystems and are of great significance for the management and protection of algal ecosystem.Materials and methodsThis study was carried out in the Hule Forest Farm (30°18'52"-30°20'55" N, 118°45'6"-118°45ʹ54ʺ E) in Ningguo city, Anhui Province, China (Fig. 1). It belongs to the hilly area of the southern Anhui Province, and has a subtropical monsoon climate, with an annual average temperature of 15.4°C and annual average precipitation of 1426.9 mm. The annual frost-free period is 226 d, the sunshine duration is 2038 h, and the average wind speed is 2.1 m/s (Wei et al., 2023). The main tree species in this forest farm were Liquidambar formosana, Cyclobalanopsis glauca, Pinus massoniana and Cunninghamia lanceolata.